Carbon nano-tube as water reducer in CDOT Class E 12 hr concrete mix. (December 2018) - Patel, Malay Mayank; Clevenger, Caroline M.; Abdallah, Moatassem
Abstract: To address maintenance and durability issues for concrete pavement, the City and County of Denver explored the use of carbon nano-tube admixtures. This research documents the hardened and fresh properties of two mix designs that use carbon nano-tube admixture as a water reducer. The authors performed compressive strength, slump and air-entrainment tests. Results indicate that the 3 gallon-per-yard (GPY) (14.85 l/m3) mix provides both the highest slump and the highest compressive strength, while meeting the air-entrainment specifications for Colorado Department of Transportation (CDOT) Class E 12 h Concrete Mix. While additional testing is recommended to evaluate long-term maintenance impacts, initial results are promising and suggest that adoption of a 3 GPY (14.85 l/m3) mix may be a viable alternative for CDOT. The contribution of this research is to document preliminary laboratory and in-situ testing of carbon nano-tube admixtures in concrete pavement mix design.